Online impulsive buying behaviour in India - Muralinathan, Swaroop (2024)
The rapid growth of e-commerce in India has led to a significant rise in online impulsive buying behavior. This study aims to evaluate the importance of impulse buying on the Internet and identify the factors and situations that contribute to this behavior in the Indian context. The research employed a mixed-methods approach, combining qualitative interviews and a quantitative survey with 241 respondents. The findings reveal that online impulsive buying is prevalent among Indian consumers, with social media advertisements and recommendations from friends and family playing a crucial role. Factors such as price competitiveness, customer reviews, and product variety significantly influence the selection of online shopping platforms. Smartphones have emerged as the primary device for online shopping, reflecting the growing importance of mobile-friendly e-commerce platforms. The study highlights the diverse range of products purchased online, with clothing, fashion accessories, electronics, and beauty products being the most popular categories. However, product returns due to mismatched expectations, damaged items, or incorrect deliveries are common. Emotional responses to impulsive online purchases vary, with many consumers expressing happiness and satisfaction, while others remain neutral. The study sample predominantly consists of young adults, employed individuals, and households with moderate to high-income levels. The findings provide valuable insights for e-commerce businesses, marketers, and policymakers in developing strategies to promote responsible consumption and ethical marketing practices related to online impulsive buying in India.